Posters and Fliers - Ricky Telg (EDIS)
WC102, a 4-page illustrated fact sheet by Ricky Telg, discusses the application of visual communications principles to the development of effective posters and fliers. Published as the second of a four-part series by the UF Department of Agricultural Education and Communication, September 2010.